2023
DOI: 10.1002/adem.202301063
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Functionalization and Hybridization of Two‐Dimensional Transition Metal Dichalcogenide for Gas Sensor

Youngjun Kim,
Inkyu Sohn,
Dain Shin
et al.

Abstract: Two‐dimensional (2D) transition metal dichalcogenides (TMDs) have garnered significant attention in gas‐sensing applications due to their sensitive response to a wide range of gas molecules and their ability to operate at low temperatures, resulting in low‐power consumption. However, there are several areas that require improvement, including insufficient sensitivity at low detection limits, limited gas selectivity, low reliability, and poor recovery. To address these issues and enhance the performance of gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 201 publications
0
3
0
Order By: Relevance
“…Donarelli et al reported 2220 s/1860 s at 150 °C, 1 ppm of NO 2 . To optimize the gas sensor performance by reducing exposure and recovery time, heterostructures, hybridization, and functionalization can be explored . Liu et al reported a 276 s recovery time in MoS 2 /ZnS heterostructure compared to over 4800 s in pure MoS 2 at 25 °C, 5 ppm of NO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Donarelli et al reported 2220 s/1860 s at 150 °C, 1 ppm of NO 2 . To optimize the gas sensor performance by reducing exposure and recovery time, heterostructures, hybridization, and functionalization can be explored . Liu et al reported a 276 s recovery time in MoS 2 /ZnS heterostructure compared to over 4800 s in pure MoS 2 at 25 °C, 5 ppm of NO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…To optimize the gas sensor performance by reducing exposure and recovery time, heterostructures, hybridization, and functionalization can be explored. 43 Liu et al 44 reported a 276 s recovery time in MoS 2 /ZnS heterostructure compared to over 4800 s in pure MoS 2 at 25 °C, 5 ppm of NO 2 . Han et al 45 reported a 74 s response time in MoS 2 /SnO 2 heterostructures instead of 165 s in pure MoS 2 at room temperature, 5 ppm of NO2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While commercially available devices are by far less diffuse than in the case of MOX, these systems can provide a manifold of functionalization/doping/decoration strategies to tailor their response to target gas molecules in view of specific applications. Finally, we present chemiresistors based on TMDs [ 21 , 22 , 23 ] as an emerging class of materials that display interesting properties in the field of gas sensing. For each sensor, we report the material of the active layer, the sensitivity, the working temperature, and the response and recovery times.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, chemical functionalization is an important way to acquire new properties and extend the applications of 2D materials. 23–28 Encouraged by the successful preparation of few-layer and monolayer h-BN, in this work, the functionalized AB-stacking h-BN bilayers were systematically investigated employing first-principles calculations, and the stability and electronic and optical properties were discussed in details. The calculations reveal that hydrogenation and hydrofluorination can significantly improve the electronic and optical properties of the AB-stacking h-BN bilayer by inducing the interfacial B–N sp 3 bonding.…”
Section: Introductionmentioning
confidence: 99%